WHEN IT OFTEN TURNS TO SILENCE: STUDENTS’ PERCEPTIONS ON ASKING QUESTIONS IN ONLINE ENGLISH CLASS AT UNIVERSITY - Atin Kurniawati (Jurnal Scientia, 2022)
This study aims at investigating the students’ perceptions on asking questions in online English class focusing on three issues: (1) the factors that encourage the students to ask questions;(2) the factors that burden the students to ask questions; and (3) the lecturers’ feedback in question and answer session. This study employed mixed-method approach by using both qualitative and quantitative data collection and analysis involving 43 students of English letters in a state Islamic university in Central Java. The results reported that the students’ interest in the subjects, the lecturers’ attitude, and lack of understanding of the learning materials are the key factors that encourage the students to ask questions. Several factors identified as the burden in asking questions are being afraid of making mistakes in speaking English, unsureness understanding of the learning materials, limited interaction, and being afraid of asking silly questions. The students reported that generally the lecturers give satisfying answers to their questions and they argue that they need more examples or quizzes from the lecturers to deepen their understanding of the learning materials.